Legal Review of Criminal Acts of Human Trafficking (Tppo) Study of Decision Number 1049/Pid.Sus/2024/PN.Mdn - Robertus Rahmat Arifin Gulo; Syaiful Khoiri Harahap; Yulkarnaini Siregar (Fox Justi : Jurnal Ilmu Hukum, 2026)
Human trafficking is a serious crime that violates human rights and human dignity. This study aims to analyze law enforcement and the judge's considerations in Decision Number 1049/Pid.Sus/2024/PN.Mdn regarding the crime of human trafficking, with a focus on the application of Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. The research method used is a qualitative case study approach, reviewing court decision documents, legal literature, and other secondary sources. The results of the study indicate that law enforcement against perpetrators of human trafficking in this decision has fulfilled the elements of the crime, namely recruitment, transportation, and exploitation, with the modus operandi being the abuse of the victim's vulnerable position. The judge's considerations are based on valid evidence, including witness statements, transaction documents, and expert analysis. The criminal sanctions imposed, namely 7 years imprisonment and a fine of Rp200,000,000, are considered proportional and in accordance with the provisions of the law. However, the study also identifies challenges in proving the elements of exploitation and protecting victims. In conclusion, this ruling reflects a serious effort to enforce the law against human trafficking, although capacity building of law enforcement officers and inter-agency coordination are needed to address the complexity of similar cases in the future. This study provides recommendations for officer training, optimizing the role of the Witness and Victim Protection Agency, and community outreach for human trafficking prevention